The Experience of the Family of the Woman with Breast Cancer: Metasynthesis - dos Anjos, Anna Cláudia Yokoyama; Fontão Zago, Marcia Maria (International Journal of Innovative Research in Medical Science, 2016)
Objective: To synthesize qualitative studies on the effects of the family‟s experience in caring for the woman with breast cancer. Method: Systematic review-Metasynthesis. Primary studies, available online, article format, Portuguese and English were included; databases: PsycInfo, PubMed, CINAHL, EMBASE and BVS. Studies were evaluated using the consolidated criteria for reporting for qualitative research (COREQ-32). Results: Final sample of 18 studies; four units of senses were built: chaos caused by the cancer; common sense and the stigma of cancer; emotions and reactions during the course of cancer; joining of forces: family‟s attitudes and strategies in the experience of caregiving. Central meaning of the experience: "maintaining the course of life by joining forces." Conclusion: In this chaotic trajectory experienced by the family, joining forces provided balance to maintain life. Further research aiming at expanding the understanding of the experience, contributing to evidence-based practice is suggested. Descriptors: Breast Neoplasms; Family; Medical Anthropology; Oncology; Qualitative Research.